Case report and analysis: Behçet’s disease with lower extremity vein thrombosis and pseudoaneurysm - Wang, Han-Lu; Zhang, Jian-Hui; Wu, Yi-Cheng; Lin, Jia-Li; Tang, Yi; Liao, Li-Sheng; Luo, Jie-Wei; Yu, Qing-Hua; Fang, Zhu-Ting (Frontiers in Immunology, 2022)
Background: Behçet’s syndrome (BS) is a unique autoimmune chronic systemic vasculitis affecting veins and arteries of all sizes. BS can lead to recurrent vascular events, especially venous thrombosis, with an incidence rate of 40%, or pseudoaneurysms formed under long-term inflammatory reaction or iatrogenic stimulation. The risk factors bring about endothelial dysfunction, platelet activation and overactivation of tissue factor leading to mural inflammatory thrombi. Thrombosis may be the first clinical manifestation of BS. Case presentation: A 32-year-old man complaining of progressive swelling and pain in the right lower extremity for 30 days was initially diagnosed with "venous thrombosis of the right lower extremity" based on color Doppler ultrasonography of the right lower extremity and underwent inferior vena cava filter placement combined with deep vein angioplasty of the right lower extremity and catheter-directed urokinase thrombolysis. Postoperative oral anticoagulant therapy was administered. However, the patient was readmitted 20 days later for pulsatile pain in the right groin. Prior medical history included 4 years of repeated oral and perineal ulcers, and 2 months of blurred vision. Abdominal CTA revealed rupture of the right common iliac artery (CIA) and left internal iliac artery (IIA), complicated by a pseudoaneurysm. Based on the clinical manifestations and other auxiliary examination results, the patient was re-diagnosed with "BS combined with deep venous thrombosis of the right lower extremity and an iliac artery pseudoaneurysm". Stent implantation was performed for an iliac artery pseudoaneurysm after the symptoms were controlled with timely immunosuppressive therapy. After endovascular treatment, the patient received continued immunosuppressive therapy and dynamic reexaminations of abdominal CTA, which revealed that a small amount of contrast agent at the stent in the right CIA continued to flow into the cavity of the pseudoaneurysm, and the size of the pseudoaneurysm was gradually enlarged compared to that post-operation. Therefore, the patient again underwent stent implantation for an iliac artery pseudoaneurysm, and the condition improved further. Conclusion: The importance of early identification of BS should be recognized, and the choice of interventional and surgical procedures should be carefully evaluated, as this may trigger further damage to vascular access in BS with aneurysm.